Age constraints on the Paleozoic Yaguarí-Buena vista succession from Uruguay: Paleomagnetic and paleontologic information - Ernesto, Marcia (2020)
The Yaguarí and the Buena Vista formations from Uruguay are historically correlated to the Brazilian Rio do Rasto and Sanga do Cabral formations, respectively, as they have some lithostratigraphic similarities, indicating a Permo-Triassic or even Triassic age of the Yaguarí-Buena Vista succession. However, they differ in the fossil indexes that characterize the faunistic communities present in both countries. A paleomagnetic work was carried out on some sections of the Buena Vista and the Yaguarí formations, as well as on some layers of bentonites, underlying the Buena Vista sediments. The alternating field and thermal demagnetization procedures revealed both normal and reversed magnetization components, but the samples showed evidence of secondary magnetic minerals and possibly remagnetizations. The calculated paleomagnetic pole for the Yaguarí-Buena Vista Formation plots near to the poles for the Choiyoi magmatism that is believed to be responsible for the bentonite accumulation; it is also in agreement with other Permian paleomagnetic poles for South America. Based on the paleomagnetic results, the available radiometric data for the bentonites, and the fossiliferous content, a Late Permian (Lopingian) age is assigned to the Yaguarí-Buena Vista rocks.